The Clinical Significance Of Circulating Mir-21, Mir-142, Mir-143, And Mir-146a In Patients With Prostate Cancer: Novel Markers of Prostate Cancer - Bolayırlı, İbrahim Murat and Önal, Bülent and Adıgüzel, Mutlu and Konukoğlu, Dildar and Demirdag, Cetin and Kurtulus, Eda Merve and Türegün, Fethi Ahmet and uzun, Hafize (Journal of Medical Biochemistry, 2021)
Prostate cancer (PCa) is the most common type of solid tissue cancer among men in western countries. To enlighten the underlying molecular mechanisms in the pathophysiology of PCa and to help the development of new diagnostics and treatment models, we planned to determine the levels of circulating miR-21, miR-142, miR-143, miR-146a, and RNU 44 levels as controls for the early diagnosis of PCa. The circulating miRNA levels in peripheral blood samples from 43 localized PCa patients, 12 metastatic PCa (MET) patients, and as a control group, 42 benign prostate hyperplasia (BPH) patients with a total of 97 volunteers were determined the by PCR method. No differences in the ΔCT values were found among the groups. In PCa and PCaMet groups the expression of miR21 and miR142 were higher compared to the BHP group. No other differences were observed among the other groups. miR21 expression in the PCa group was 6.29 folds upregulated whereas in the PCaMet group 10.84 folds upregulated. When the total expression of miR142 is evaluated, it showed a positive correlation with mir21 and mir 146 (both p<0.001). Also, the expression of miR146 shows a positive correlation with both miR21 and miR143 (both p<0.001). Expression of miRNAs was found to be an independent diagnostic factor in patients with Gleason score, PSA, and free PSA levels. In conclusion, our study showed that co-expression of miR-21, miR-142, miR-143, and miR-146a and the upregulation of miR-21 resulted in increased prostate carcinoma cell growth. In the PCaMet group, miR21 is the most upregulated of all miRNAs. These miRNA markers that are expressed in different levels may provide a novel diagnostic tool to help diagnose PCa with aggressive behavior.